Structural elements of stromal interaction molecule function. (July 2018) - Novello, Matthew J.; Zhu, Jinhui; Feng, Qingping; Ikura, Mitsuhiko; Stathopulos, Peter B.
Graphical abstract: Highlights: The luminal domains maintain STIM quiescence via EF-hand:SAM domain interactions. A dynamic exchange of cytosolic coiled-coil interactions underlies STIM1 activation. Glycosyl-, glutathionyl- and phosphorylation regulate STIM structure and function. Abstract: Stromal interaction molecule (STIM)-1 and -2 are multi-domain, single-pass transmembrane proteins involved in sensing changes in compartmentalized calcium (Ca 2+ ) levels and transducing this cellular signal to Orai1 channel proteins. Our understanding of the molecular mechanisms underlying STIM signaling has been dramatically improved through available X-ray crystal and solution NMR structures. This high-resolution structural data has revealed that intricate intramolecular and intermolecular protein-protein interactions are involved in converting STIMs from the quiescent to activation-competent states. This review article summarizes the current high resolution structural data on specific EF-hand, sterile α motif and coiled-coil interactions which drive STIM function in the activation of Orai1 channels. Further, the work discusses the effects of post-translational modifications on the structure and function of STIMs. Future structural studies on larger STIM:Orai complexes will be critical to fully defining the molecular bases for STIM function and how post-translational modifications influence these mechanisms.